Media multitasking, impulsivity and dual task ability. (March 2019) - Shin, Myoungju; Webb, Andrew; Kemps, Eva
Abstract: With recent developments in technology, media multitasking is an ever-increasing phenomenon. Although most studies associate media multitasking with high impulsivity and poorer cognitive performance, findings in the literature have been mixed, with some studies suggesting the opposite. The aim of this study was to investigate the relationship between media multitasking and the capacity to exert inhibitory control, as well as the ability to multitask in a multisensory setting. Results showed that media multitasking was associated with high attentional impulsivity and lower initiatory self-control, but not with inhibitory self-control. Relatedly, heavy media multitaskers were slower and showed more omission errors on the go/no-go task, suggestive of inattention; however, they were better at inhibiting already initiated motoric responses in the stop signal task. Media multitasking was further associated with faster responses when a letter and a tone task were temporally separated, but not when they were presented closer in time. Taken together, the results suggest a more nuanced relationship between media multitasking, personality and cognitive ability than has previously been thought. This has important real life implications for media multitasking, showing both advantages and disadvantages. Highlights: Media multitasking was linked to initiatory but not inhibitory self-control. Heavy multitaskers were impulsive, inattentive, but inhibited motor responses better. Multitasking was linked to better dual task ability with tasks temporally separated.